What Role Does Type of Sponsorship Play in Early Integration Outcomes? Syrian Refugees Resettled in Six Canadian Cities - Hynie, Michaela; McGrath, Susan; Bridekirk, Jonathan; Oda, Anna; Ives, Nicole; Hyndman, Jennifer; Arya, Neil; Shakya, Yogendra B.; Hanley, Jill; McKenzie, Kwame (Refuge, 2019)
There is little longitudinal research that directly compares the effectiveness of Canada’s Government-Assisted Refugee (GAR) and Privately Sponsored Refugee (PSR) Programs that takes into account possible socio-demographic differences between them. This article reports findings from 1,921 newly arrived adult Syrian refugees in British Columbia, Ontario, and Quebec. GARs and PSRs differed widely on several demographic characteristics, including length of time displaced. Furthermore, PSRs sponsored by Groups of 5 resembled GARs more than other PSR sponsorship types on many of these characteristics. PSRs also had broader social networks than GARs. Sociodemographic differences and city of residence influenced integration outcomes, emphasizing the importance of considering differences between refugee groups when comparing the impact of these programs.